Visible-Light-Mediated Tandem Sulfonylation/Cyclization of Vinyl Azides with Sulfonyl Hydrazines for the Synthesis of 6-(Sulfonylmethyl)phenanthridines under Mild Conditions - Mao, Liu-Liang; Quan, Li-Xia; Zhu, Xian-Hong; Ji, Cong-Bin; Zhou, An-Xi; Chen, Fayun; Zheng, Da-Gui (Synlett, 2019)
A visible-light-mediated tandem sulfonylation/cyclization of vinyl azides with sulfonyl hydrazines was developed that provides an efficient and simple strategy for the synthesis of valuable 6-(sulfonylmethyl)phenanthridines with a broad substrate scope and satisfactory yields under mild conditions.
Keywords: photochemical reaction; tandem reaction; sulfonylation; cyclization; sulfonyl hydrazines; phenanthridines